The Chinese traders of Bacolod City - Bitanga, Sherman Hinlo
This study on "The Chinese Migrants of Bacolod city" documents and analyzes factors which motivated chinese settlement in the city of Bacolod and their integration into the mainstream of Philippines society. It sheds light and a deeper understanding about their Chineseness and to the history of Chinese migrants in Capitol shopping Center, Bacolod City., The most recent Chinese migration to Bacolod City began after World War II. The pioneer migrants were those who put up business establishments in different parts of Bacolod city. The establishment of Capitol shopping Center as the new commercial locale after 1955 fire which destroyed the commercial are of Bacolod City, attracted these Chinese migrants to transfer their business into the area. These migrants predominantly came from the southeastern provinces of China, namely, Fukien and Kwangtung. Most of these migrants hail from the cities of Amoy (Fukien) and Canton (Kwangtung). The migrants who followed were relatives and neighbors who preferred to settle in Capitol shopping Center, Bacolod City. This where the greatest concentration of Chinese in Bacolod are found and where the greatest number of Chinese owned and operated business establishment are located. The Chinese migrants live scattered within the said community. At present time, only a few of the original Chinee migrants continue to live in the area. Some of them, especially the youngest generation of Chinese immigrants, live in other parts of Bacolod City and consider themselves well integrated into their new home area. The migrants made adjustments to their new social system. The hardships and problems they encountered at their place of settlement, were due to their distinct culture and adherence to their Chineseness. Ideas and external behaviors of second-generation migrants reveal that the Chinese residents of Bacolod City have largely adopted to the ways of Filipinos. Because of close and constant interactions that they have with the native residents, the younger generation of Chinese migrants show less adherence to their Chineseness than the pioneers who continued to concentrate on the affairs of their business and homes.